Effect of computerised evidence based guidelines on management of asthma and angina in adults in primary care: cluster randomised controlled trial. Issue 7370 (26th October 2002) - Eccles, Martin; McColl, Elaine; Steen, Nick; Rousseau,, Nikki; Grimshaw, Jeremy; Parkin,, David; Purves, Ian
Abstract : Abstract: Objective: To evaluate the use of a computerised support system for decision making for implementing evidence based clinical guidelines for the management of asthma and angina in adults in primary care. Design: A before and after pragmatic cluster randomised controlled trial utilising a two by two incomplete block design. Setting: 60 general practices in north east England. Participants: General practitioners and practice nurses in the study practices and their patients aged 18 or over with angina or asthma. Main outcome measures: Adherence to the guidelines, based on review of case notes and patient reported generic and condition specific outcome measures. Results: The computerised decision support system had no significant effect on consultation rates, process of care measures (including prescribing), or any patient reported outcomes for either condition. Levels of use of the software were low. Conclusions: No effect was found of computerised evidence based guidelines on the management of asthma or angina in adults in primary care. This was probably due to low levels of use of the software, despite the system being optimised as far as was technically possible. Even if the technical problems of producing a system that fully supports the management of chronic disease were solved, there remains the challenge of integrating the systems into clinical encounters where busy practitioners manage patients with complex, multiple conditions.